USING MEDIA CONTENTS IN TEACHING ENGLISH LANGUAGE (Multidisciplinary Journal of Science and Technology, 2024)
This article explores the effective incorporation of media content into English language teaching, providing a comprehensive guide on various media types and their educational benefits. The discussion covers the utilization of movies, TV shows, music, podcasts, news, documentaries, interactive games, mobile apps, social media, and blogs to enhance language skills and cultural understanding. Each medium is analyzed for its potential to improve specific linguistic competencies such as listening, speaking, reading, and writing. The article emphasizes the role of media in making learning engaging and culturally rich, addressing different learning styles and levels of language proficiency. By integrating media into English language instruction, educators can offer a more dynamic and contextual learning experience that aligns with modern educational needs.